Regionalisation of measures shaping the rural space in agricultural producers’ opinions – a case study with Mazowieckie Voivodeship as an example - Kocur-Bera, Katarzyna (International Conference “Environmental Engineering”, 2017)
In recent years, the economic situation in rural areas has changed a lot. Poland’s accession to the European Union opened up a lot of possibilities for agricultural farms. Thanks to the implemented Union projects such as the Rural Development Programme 2007–2013 (RDP 2007–2013), the Human Capital Operational Programme 2007–2013 (HCOP 2007–2013), and the Regional Operational Programme for Mazowieckie Voivodeship 2007–2013 (ROP 20072013), local authorities may apply for funding aimed at the improvement of life situation of the rural population. The aim of this paper was to provide an answer to the question: how is the influence of the RDP 2007–2013 and other Union programmes for furnishing agricultural activities perceived by owners of agricultural farms? For the analysis, statements of inhabitants of Krasne, Krzynowłoga Mała, Jednorożec and Czernice Borowe communes, obtained by direct interview using a questionnaire were chosen. The respondents unanimously stated that the Union funds obtained under the PROW 2007–2013 provided a lot of benefits. The financial support obtained for the implementation of furnishing of agricultural activities was assigned for the development of rural areas. Farmers obtained new prospects for development and modernisation of farms, which increased their competitiveness in the market. Today, the previously forgotten rural areas are developed, and ready for changes and new activities. Support for the agricultural sector is of fundamental significance to the economy of the entire country, as thanks to these investment projects Poland is competitive in the market, and the revitalised agricultural areas have become an attractive tourist destination.
Keywords: regionalisation; rural areas; development; Union projects